Virtual instrument for estimation of HVAC and HVDC test parameters according to IEC 60060-1:2010 - Oliveira, Yuri Reis; Silva, Márcio Thelio; Barbosa, Carlos Roberto Hall (Journal of physics. Conference series, 2021)
High and ultra high voltage tests are commonly carried out to determine external and internal dielectric performances of electric power equipment. The standardization of these tests in different laboratories is obtained by following the standards with the requirements necessary to perform the tests. Among such requirements, the test voltage parameters must be measured within acceptable uncertainties. For a correct analysis of the test and presentation of the results it is necessary that the measuring system and the instrument used be able to estimate all parameters according to standard IEC 60060-1:2010, depending on each type of voltage and test, AC, DC or impulse. However, simpler conventional instruments, such as multimeters, are not capable of measuring and indicating all parameters required by current standards. Thus, dedicated instruments and software are needed, capable of performing the analysis of these parameters within the acceptable uncertainty limits. The use of software or measurement algorithms for voltage impulse testing is already described in IEC 61083-1 and -2 standards. Specifically, part 2 presents the reference waveforms used for the validation of the software used in the tests. Similarly, IEC 61083-4 is being developed for high voltage AC and DC tests, with standard waveforms for validation of the measurement software. The objective of this work is presenting the HVAT AC-DC virtual instrument developed in LabVIEW environment, capable of estimating the required AC and DC test parameters of the ABNT NBR IEC 60060-1:2013 standard and analyzing the robustness of such a virtual instrument through low and high voltage tests.